Induced Neurons for Disease Modeling and Repair: A Focus on Non-fibroblastic Cell Sources in Direct Reprogramming - Kim, Kathryn M.; Thaqi, Mentor; Peterson, Daniel A.; Marr, Robert A. (Frontiers in Bioengineering and Biotechnology, 2021)
Direct cellular reprogramming exhibits distinct advantages over reprogramming from an induced pluripotent stem cell intermediate. These include a reduced risk of tumorigenesis and the likely preservation of epigenetic data. In vitro direct reprogramming approaches primarily aim to model the pathophysiological development of neurological disease and identify therapeutic targets, while in vivo direct reprogramming aims to develop treatments for various neurological disorders, including cerebral injury and cancer. In both approaches, there is progress toward developing increased control of subtype specific production of induced neurons. A majority of research primarily utilizes fibroblasts as the donor cells. However, there are a variety of other somatic cell types that have demonstrated the potential for reprogramming into induced neurons. This review highlights studies that utilize non-fibroblastic cell sources for reprogramming, such as astrocytes, olfactory ensheathing cells, peripheral blood cells, Müller glia, and more. We will examine benefits and obstructions for translation into therapeutics or disease modeling, as well as efficiency of the conversion. A summary of donor cell, induced neuron types, and methods of induction is also provided.